Bridging Faith and Innovation: A Systematic Literature Review of Islamic FinTech Adoption Patterns and Regulatory Frameworks (2020-2024) - Suswanto, Riza Eko; Wahyudi, Ickhsanto; Rahmawati, Rahmawati; Said, Muhammad (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This systematic literature review critically examines the adoption and regulatory frameworks of Islamic Financial Technology (Islamic FinTech) across various jurisdictions between 2020 and 2024. Through an extensive analysis of 28 scholarly articles, the study identifies the key factors influencing adoption, regulatory challenges, and potential growth opportunities in the Islamic FinTech sector. The findings reveal that trust, religious orientation, and technological readiness significantly influence Islamic FinTech adoption. Additionally, the study identifies critical challenges, including Shariah compliance mechanisms, regulatory frameworks, and consumer protection. The novelty of this study lies in its systematic and holistic approach, integrating the analysis of adoption factors, regulatory challenges, and technological innovations within the context of Islamic FinTech. The research emphasizes the importance of developing a comprehensive regulatory framework that balances technological innovation with Shariah compliance, while ensuring consumer protection. This study contributes to the advancement of knowledge on Islamic FinTech by providing practical insights for policymakers, practitioners, and researchers in developing a sustainable Islamic FinTech ecosystem. Furthermore, the study offers concrete recommendations, such as the harmonization of international Shariah standards and the utilization of blockchain technology to enhance transparency, which can be applied in a global context.